Demography and Viability of a Hunted Population of Polar Bears - Taylor, Mitchell K.; Laake, Jeff; McLoughlin, Philip D.; Born, Erik W.; Cluff, H. Dean; Ferguson, Steven H.; Rosing-Asvid, Aqqalu; Schweinsburg, Ray; Messier, François (ARCTIC, 2010)
We estimated demographic parameters and harvest risks for a population of polar bears (Ursus maritimus) inhabiting Baffin Bay, Canada and Greenland, from 1974 to 1997. Our demographic analysis included a detailed assessment of age- and sex-specific survival and recruitment from 1221 marked polar bears, which used information contained within the standing age distribution of captures and mark-recapture analysis performed with Program MARK. Unharvested (natural) survival rates for females (± 1 SE) from mark-recapture analysis were 0.620 ± 0.095 (cubs), 0.938 ± 0.042 (ages 1–4), 0.953 ± 0.020 (ages 5–20), and 0.919 ± 0.046 (ages 21+). Total (harvested) survival rates for females were reduced to 0.600 ± 0.096 (cubs), 0.901 ± 0.045 (ages 1–4), 0.940 ± 0.021 (ages 5–20), and 0.913 ± 0.047 (ages 21+). Mean litter size was 1.59 ± 0.07 cubs, with a mean reproductive interval of 2.5 ± 0.01 years. By age 5, on average 0.88 ± 0.40 of females were producing litters. We estimated the geometric means (± bootstrapped SDs) for population growth rates at stable age distribution as 1.055 ± 0.011 (unharvested) and 1.019 ± 0.015 (harvested). The model-averaged, mark-recapture estimate of mean abundance (± 1 SE) for years 1994–97 was 2074 ± 266 bears, which included 1017 ± 192 females and 1057 ± 124 males. We incorporated demographic parameters and their error terms into a harvest risk analysis designed to consider demographic, process, and sampling uncertainty in generating likelihoods of persistence (i.e., a stochastic, harvest-explicit population viability analysis). Using our estimated harvest of polar bears in Baffin Bay (88 bears/yr), the probability that the population would decline no more than could be recovered in five years was 0.95, suggesting that the current hunt is sustainable. De 1974 à 1997, on a évalué les paramètres démographiques d’une population d’ours polaires (Ursus maritimus) habitant la baie de Baffin (Canada et Groenland), ainsi que les risques associés à leur prélèvement. Notre analyse démographique ...